Rancang Bangun Aplikasi E-Musrenbang Pada Desa Jungai Berbasis Web - Rihana, Rihana; Iwan Setiawan; Ariansyah Ariansyah (Jurnal Publikasi Teknik Informatika, 2023)
The development of technology is getting faster and faster, especially information and communication technology. Information systems are no longer a foreign thing today. Utilization of this technology is also very useful and needed in producing information regarding musrenbang in Jungai Village. The problem that occurs in musrenbang activities in Jungai village is the relatively low level of community involvement and lack of community participation in musrenbang activities. In addition, the office has not been optimal in accommodating community proposals and aspirations in village development. In conducting this research using qualitative research whose purpose is to describe what is currently happening. So that the data will be obtained to support the preparation of the research report. While in this study the method used by the author is a qualitative descriptive method which is a research method that utilizes qualitative data and is described descriptively with the aim of describing or describing the results of existing research. The software development method that the author uses is the Waterfall model. While the analysis and design tools use UML (Unified Modeling Language) consisting of use case diagrams, class diagrams and activity diagrams. This application can make it easy for people with circumstances or conditions who are unable to come directly to the Jungai Village office to carry out musrenbang activities.